Pre-enrichment effect on PCR Detection of Salmonella Enteritidis in artificially-contaminated raw chicken meat - Abdul Talib, Mohd Afendy; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Salmonella remains to be a major foodborne pathogen for animals and humans and is the leading cause of foodborne infections and outbreaks in various countries. Salmonella Enteritidis is one of the most frequently isolated serotypes in poultry and poultry products from human food poisoning cases. It can cause mild to acute gastroenterititis as well as other common food poisoning symptoms when infection takes place in human. Nucleic acid amplification technologies such as Polymerase Chain Reaction (PCR) is a tool that is rapid and sensitive for detection of bacterial pathogen. We report the successful detection of S. Enteritidis by PCR in raw chicken meat artificially-contaminated with serial concentration of S. Enteritidis using crude DNA extracts as DNA template. PCR primers, ENT-F and ENT-R targeted on sdfI gene were used to amplify DNA region unique to S. Enteritidis with crude DNA extract of the samples, yielded product with the size of 303 bp. These primers were specific to S. Enteritidis when tested by in-silico simulation against genome database of targeted bacterial species and confirmed in PCR as amplification bands were observed with S. Typhimurium, S. Polarum and S. Gallinarum. The established PCR can detect as few as 9.4 X 101 CFU/ml of inoculated S. Enteritidis concentration and proved that pre-enrichment effect have significant effect on PCR detection by increasing 1000-fold of the sensitivity limit compared to the non pre-enriched samples. The PCR technique indicated that it can be successfully coupled with pre-enrichment step to offer advantage in routine screening and surveillance of bacterial contamination in food samples.